Pharmacogenetics in breast cancer: steps toward personalized medicine in breast cancer management - Sarah Rofaiel; Esther N Muo; Shaker A Mousa (Dove Medical Press, 2010)
Sarah Rofaiel1, Esther N Muo1, Shaker A Mousa1,21The Pharmaceutical Research Institute, Albany College of Pharmacy and Health Sciences, Albany, New York, USA; 2King Saud University, Riyadh, Saudi ArabiaAbstract: There is wide individual variability in the pharmacokinetics, pharmacodynamics, and tolerance to anticancer drugs within the same ethnic group and even greater variability among different ethnicities. Pharmacogenomics (PG) has the potential to provide personalized therapy based on individual genetic variability in an effort to maximize efficacy and reduce adverse effects. The benefits of PG include improved therapeutic index, improved dose regimen, and selection of optimal types of drug for an individual or set of individuals. Advanced or metastatic breast cancer is typically treated with single or multiple combinations of chemotherapy regimens including anthracyclines, taxanes, antimetabolites, alkylating agents, platinum drugs, vinca alkaloids, and others. In this review, the PG of breast cancer therapeutics, including tamoxifen, which is the most widely used therapeutic for the treatment of hormone-dependent breast cancer, is reviewed. The pharmacological activity of tamoxifen depends on its conversion by cytochrome P450 2D6 (CYP2D6) to its abundant active metabolite, endoxifen. Patients with reduced CYP2D6 activity, as a result of either their genotype or induction by the coadministration of other drugs that inhibit CYP2D6 function, produce little endoxifen and hence derive limited therapeutic benefit from tamoxifen; the same can be said about the different classes of therapeutics in breast cancer. PG studies of breast cancer therapeutics should provide patients with breast cancer with optimal and personalized therapy.Keywords: pharmacogenomics, genetic, pharmacokinetic, pharmacodynamic, personalized medicine, pharmacotherapy, anticancer drugs, efficacy, safety